The role of computed tomography in the diagnosis of malperfusion syndrome in acute aortic dissection (literature review) - A. M. Nunaeva; O. A. Zabavskaya; R. Sh. Muslimov; L. T. Khamidova; L. S. Kokov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Timely diagnosis and treatment of patients with acute aortic dissection continues to be one of the most important and discussed problems in emergency medicine. Due to accurate diagnosis and an effective surgical approach, the results of interventions for acute aortic dissection have improved, at least in specialized centers. However, for patients suffering from malperfusion against the background of acute dissection, the prognosis in some cases remains unfavorable. The cause of malperfusion can be stenosis or occlusion of the main branches of the aorta, which can be detected using computed tomography aortography (CT-AG). Today, it is the method of choice in the diagnosis of not only acute aortic dissection, but also its complications, including malperfusion ones. The purpose of this article is to analyze the capabilities of CT-AG in detecting various types of stenosis arising in the transition of dissection to the main branches of the aorta, as well as the actual manifestations of malperfusion in organs and tissues in acute aortic dissection, according to various authors.